Treatment outcomes and factors associated with open arthrotomy in bacterial septic arthritis patients at NongKhai Hospital - Tinnahaphat, Jintara (Health Science, Science and Technology Reviews, 2024)
Bacterial septic arthritis is a medical emergency condition. Some studies have shown that the surgical and the non-surgical methods result in similar treatment outcomes. Meanwhile, some studies have found that patients treated by the surgical method have significantly longer lengths of stay but a lower mortality rate than patients treated by the non-surgical method. This study therefore aimed to determine treatment outcomes and factors associated with open arthrotomy in bacterial septic arthritis patients at NongKhai Hospital. The study methodology was descriptive. Factors analysis was conducted using Univariate analysis, and only factors with p<0.20 were further analyzed using Multiple logistic regression with statistical significance at p<0.05. 201 eligible patients were enrolled of which 40 patients were treated by non-surgical method, and 161 patients were treated by open arthrotomy. According to the current study, univariate analysis of the data revealed nine factors associated with open arthrotomy including diabetes mellitus, chronic kidney disease, steroid use, prior joint injury within a 1-month, prior treatment, white blood cell counts in blood ≥10,000 cells/mm³, white blood cell counts in synovial fluid ≥100,000 cells/mm³, positive synovial fluid culture, and cellulitis (p<0.20). Further multiple logistic regression analysis of these factors revealed only one statistically significant factor which is prior treatment (p=0.012, 95% CI 1.269-7.148, Adjusted OR=3.011). As for treatment outcomes, there is no significant difference between the open arthrotomy and non-surgical groups. However, it was found that the open arthrotomy group had a longer length of stay and higher cost of treatment than the non-surgical groups statistically significant.